Implementation of Case-based Learning with Contextual Approach to Improve students’ Problem-Solving Skills - Lukman, Tazkia Alya; Kaniawati, Ida; Suyana, Iyon (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2025)
This research aimed to investigate the implementation of Case-Based Learning (CBL) with a contextual approach to enhance students’ problem-solving skills in dynamic fluids. The study employed a pre-experimental design with a one-group pretest-posttest, involving 33 eleventh-grade students from a senior high school in Bandung. A 20-item essay test assessed five aspects of problem-solving skills based on Heller’s (1992) framework: visualize the problem, physics description, plan a solution, execute the plan and check and evaluate. Data analysis included N-gain, Wilcoxon signed-rank test, and effect size (Cohen’s d). Results indicated that students’ problem-solving skills improved moderately across all aspects, with an average N-gain of 0.5. The Wilcoxon test revealed a significant increase in posttest scores (p < 0.05), and the effect size was very high (d = 2.6), indicating a strong impact of the intervention. These findings demonstrate that the implementation of CBL with a contextual approach is effective in enhancing students’ problem-solving skills, fostering deeper understanding, and promoting active engagement in learning dynamic fluids.